Penerapan Model Scramble dalam Pembelajaran Teks Berita Bahasa Indonesia - Larasati, Putti; Putrayasa, Ida Bagus; Dewantara, I Putu Mas (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The Merdeka Curriculum is a curriculum with diverse extracurricular learning where the content will be more optimal so that students have sufficient time to deepen concepts and strengthen competencies. However, in practice in schools, especially in junior high schools that have implemented the Merdeka curriculum, it turns out that there are still many students who experience difficulties in understanding and mastering learning. One of them is learning Indonesian. This research aims to analyze the application of the scramble-type cooperative model in learning news texts.Method – This research uses a qualitative descriptive research design. The sample in this study amounted to 170 respondents. The instruments used in this research are observation and interview instruments to collect data related to the research. The data validity technique used in this research includes testing the credibility of the data by triangulation by presenting the data in the form of narrative text.Findings – Based on the research results, it was concluded that the Scramble cooperative learning model could increase students' activeness, critical thinking, and interest, which ultimately influenced student learning outcomes in learning Indonesian in the classroom. The use of the Scramble learning model triggers student activity, thus changing a class of passive students into active ones. However, the Scramble cooperative learning model has several obstacles faced by teachers, such as the need for time to prepare, the difficulty of conditioning students, the teacher must understand the character and abilities of students and the class becomes noisy. Research Implications – This research implies that teachers need to further improve their professionalism, namely by improving teaching methods that are good and enjoyable for students.